Pengamalan Nilai Profil Pelajar Pancasila Dalam Proses Pembelajaran Pada Era Digital Di SMPN 6 Palangka Raya - Gabriela Elsa Putri; Misnawati Misnawati; Dara Syahadah; Yustina Sari; Rustiana Ummy; Ika Nurfitria (Universitas 45 Surabaya, 2023)
Pancasila is the basis of the state as well as the guideline for the life of the Indonesian nation which will always be attached throughout life. In this case, it can be understood that Pancasila is needed by society as a benchmark in behaving, as well as regulating the state order. As a national identity, Pancasila is not only conveyed in one generation, however, Pancasila is a hereditary heritage for the younger generation. As for continuing it, Pancasila is given in the form of character education which is introduced in the scope of education. Through Pancasila as character education, Indonesian people are able to realize Pancasila values in life. In realizing character education, the Ministry of Education and Culture (Kemendikbud) designed the Merdeka curriculum which included the Pancasila Student Profile. The Pancasila Student Profile is the embodiment of Indonesian students as lifelong students who have global competence and behave in accordance with Pancasila values. This study aims to analyze the practice of the values contained in the Pancasila Student Profile in the SMPN 6 Palangka Raya school environment. The results found that SMPN 6 Palangka Raya implemented the Pancasila Student Profile well in the school environment.